Mengungkap Implementasi Asas Kekeluargaan terhadap Benda Jaminan dalam Kontrak Kredit di Koperasi Simpan Pinjam Ratna Dana - Gusti Ayu Ketut Rencana Sari Dewi; Putu Riesty Masdiantini (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
Cooperative is an organization whose members consist of individuals or business entities that have legal aspects with a people's economic movement based on the principle of kinship. The principle of kinship is defined as a reflection of oneself on moral awareness and responsibility for cooperatives. Therefore, it is important to carry out efforts to reveal in depth the principles of kinship in the Ratna Dana Cooperative. In addition, efforts to treat debtor collateral objects in accordance with credit agreements are important to know, even more so in the current Covid-19 pandemic. The subjects in this study were the Cooperative Management consisting of the Chairperson, Secretary, Treasurer, and Staff of the Credit Division. This study uses observation, interviews, and documentation methods, and the object of research is KSP Ratna Dana's internal data related to procedures for handling bad loans. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The Ratna Dana Savings and Loans Cooperative has implemented the principle of kinship well, be it the principle of kinship to the debtor or to the debtor's collateral. However, the Ratna Dana Savings and Loans Cooperative has not yet implemented an auction for the debtor's collateral in accordance with the credit agreement.